Peran Usaha Mikro Kecil dan Menengah (UMKM) Dalam Pengentasan Kemiskinan - Muhammad Faris Hermawan; Rizna Salsabila; Iqbal Maulana Saputra (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
This study aims to discuss the important role of Micro, Small and Medium Enterprises (MSMEs) in poverty reduction efforts in Indonesia. Poverty is a complex and multidimensional social problem that requires a comprehensive approach to overcome its challenges. MSMEs, as the backbone of the Indonesian economy, have great potential to be agents of change in reducing poverty levels. The subjects of this study are MSMEs that contribute to poverty reduction in Indonesia. The data collection technique in this study uses a library technique that takes multiple sources as references such as books, national journals, etc. The results of this study suggest that it can serve as a basis for developing sustainable policies to support MSMEs as one of the strategic solutions to overcome poverty in Indonesia.